Digital Platform Power Play: Indonesian and European Union Law Perspective - Hufron Hufron; Sultoni Fikri; Syofyan Hadi; Ievgenii Shulga; Agung Satryo Wibowo (Universitas Negeri Semarang, 2024)
Plenty aspect of human life across various regions, also Indonesia, utilizes electronic systems for a multitude of activities, and involving digital platforms. The concept of Digital Platform Powerplay is linked to the digital market and personal data protection. In Indonesia, the regulatory framework governing digital markets and personal data primarily relies on Law No. 11/2008 concerning Electronic Information and Transactions, which has undergone two amendments: Law No. 19/2016 amending Law No. 11/2008, and Law No. 1/2024 amending Law No. 11/2008 for the second time and Law No. 27/2022 concerning Personal Data Protection. As a implementation regulation Government Regulation No. 80/2019 concerning Electronic Commerce and Government Regulation No. 71/2019 concerning the Implementation of Electronic Systems and Transactions further elaborate on these regulations. These legal provisions are intended to provide legal certainty for users. It is essential to review all regulations related to electronic systems and digital platforms by comparing them with the regulatory frameworks in the European Union. The study addresses two primary issues: 1) the legal regulation of digital markets from the perspective of Indonesian positive law, and 2) the legal regulation of digital markets from the perspective of European Union law. This research employs normative legal research methodologies, utilizing both statutory and comparative approaches. The findings of this study suggest that Indonesia should consider adopting the European Union's Digital Markets Act and Personal Data Protection regulations by amending Law No. 11/2008 concerning Electronic Information and Transactions and its amendments, with particular emphasis on aspects related to Digital Platform Powerplay.